Design study of a tailless glider - Buchanan, E.J. (Cranfield University, 1975)
The important theoretical parameters in the design of a high performance tailless sailplane have been determined. Inter-relationships between these parameters have been discovered and are shown on a work study flow chart. The design specification demanded, a. equal, or better, achieved cross-country performance, than a conventional sailplane of equal span, and, b. satisfactory stability and control. The 15 metre, standard. class, Standard Cirrus sailplane, was used as a basis for comparison of performance, stability and control. The design study revealed a tailless sailplane with a calculated 10% performance gain. The rigid aircraft, longitudinal stability and control analysis showed the aircraft to be more dependent on centre of gravity location but capable of simulating the Standard Cirrus. Yaw control posed a problem, but the severest encounter involved the longitudinal dynamics of the flexible wing. Wing structural layout will hopefully eliminate this problem. During the course of the study the 15 metre class was widened to allow the use of flaps. This became a necessary feature of the tailless design and the performance increment is likely to be similar.
Keywords: sailplanes; tailless; aircraft design; high performance; stability; yaw control; aircraft performance; longitudinal dynamics; flaps